DI-010 The importance of reporting lack of therapeutic response: the olanzapine case in the Syracuse Provincial Health Authority, Italy. (24th February 2014) - Avola, N; Guzzardi, S; Spadaro, D; Marletta, E; Valerio, A; Regolo, S; Sgarlata, D
Abstract : Background: In Syracuse PHA from 01/11/2007 the drug olanzapine (Zyprexa) was dispensed by the National Health System, in accordance with AIFA guidelines. In October 2011 the generic drug was introduced in the AIFA transparency lists and since February 2012 Syracuse PHA has dispensed Teva generic olanzapine. Purpose: Because of the distrust in Italy about generics, the authors collected information about possible adverse reactions to originator and generic olanzapine. Materials and methods: The authors collected the spontaneous Adverse Drug Reactions (ADRs) that were reported in Syracuse PHA, from 01/11/2007 to 31/05/2013. Results: From 01/11/2007 to 31/01/2012 767 patients were prescribed Zyprexa 10 mg, from 01/02/2012 to 31/05/2013 63 patients were prescribed olanzapine 10 mg generic, of these all 63 patients switched from originator to generic. 8 reports were received and concerned 7 males and 1 female, between 18 and 51 years old. Olanzapine was prescribed for: psychotic disorder, chronic schizophrenia, bipolar disorder (maniac depression), disorganised schizophrenia. The reports were: – 6 lack of therapeutic response to the generic drug (daily dose: 10 mg in 3 reports and 20 mg in the other 3), the consequences were: 1 non-fatal, 3 serious with life-threatening consequences and 2 serious with hospitalisation or prolongation of hospitalisation. In all cases treatment was discontinued and the pathological conditions improved. One patient restarted Zyprexa 10 mg. – 1 case of psychotic decompensation, confusion with life-threatening consequences, after administration of 10 mg generic olanzapine. It was discontinued and Zyprexa 10 mg was again prescribed with improvement of psychopathological condition. In fact the patient, for several years, was treated steadily with Zyprexa 10 mg, maintaining good mental compensation. – The 1 report on Zyprexa 10 mg concerns a patient aged 37, who attempted suicide with a drugs overdose: Zyprexa 10 mg, Invega 9 mg, Nozinan 25 mg and Felison 30 mg. Conclusions: 1/8 reports was about Zyprexa, and 75% reported the ineffectiveness of the generic. Pharmacists are under great pressure to buy generics, whose therapeutic equivalence is guaranteed by AIFA. Reporting the ADRs and ineffectiveness are critical to clarifying the real therapeutic equivalence between generic and originator. No conflict of interest.